The moderating effect of geographical scope on the relationship between managers' prior international knowledge and working experience and international performance in the Malaysian halal food industry - Ismail, Noor Azlin; Mohamed, Zainal Abidin; Uli, Jegak (Universiti Putra Malaysia Press, 2013)
This study investigates the moderating effects of geographical scope level (measured by number of regional bases) on the relationship between managers' prior international knowledge and working experience and international performance among small and medium enterprises in the Malaysian Halal Food Industry. Previous studies have stressed that experiential knowledge is an essential resource for a firm's internationalization process from both the traditional Stage Theory based on incremental and international entrepreneurship on born global rapid internationalization perspectives. Unfortunately, most of the studies did not empirically investigate the influence of scope level as a moderator on the relationship between international performance and managers' prior international knowledge and working experience. The findings of this study reveal that firms that export regionally (lower scope) have lower experiential knowledge and international performance compared to firms that export globally (higher scope). As a result, there are differences in terms of the internal capability among these two types of small and medium enterprises as a source of their competitive advantage in foreign markets.